Associations Between Severe Obesity and Depression: Results From the National Health and Nutrition Examination Survey, 2005-2006 - Arlene M. Keddie, PhD, MSPH (Centers for Disease Control and Prevention, 2011)
IntroductionMy objectives were to investigate the association between obesity and depression in a representative sample of American adults, investigate sex and severity of obesity as modifiers of the association between depression and body mass index, determine whether large waist circumference is associated with depression, and explore whether specific health behaviors and poor physical health are possible mediators of the association between obesity and depression, if found.MethodsThe sample consisted of 3,599 nonpregnant adults aged 20 years or older from the National Health and Nutrition Examination Survey, 2005-2006. I operationalized obesity as body mass index (BMI) and waist circumference from the anthropometric measurements of participants and current depression from Patient Health Questionnaire (PHQ-9) scores. I ran logistic regression models with depression as the dependent variable.ResultsIn unadjusted analyses, large waist circumference (≥88 cm for women and ≥102 cm for men) and class III obesity (BMI ≥40 kg/m2) were associated with higher prevalence of depression in women only. All of these associations dramatically weakened after adjusting for demographic factors, self-rated health status, and number of chronic conditions.ConclusionThese findings support an association between depression and obesity in women who are severely obese. Future studies should investigate poor physical health as a possible mediator of the association between obesity and depression in this population of women.